KECERDASAN BUATAN MANUSIA (ARTIFICIAL INTELLIGENCE); TEKNOLOGI IMPIAN MASA DEPAN - Kusumawati, Ririen (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
The computer technology has incredibly increased. Computer software and hardware compete to meet the customer's needs. The research intends to spread the knowledge of information technology, specifically, on the artificial intelligence. The concept of artificial intelligence is adopting and imitating human form, character, and habit which to be implemented on the computer. Using natural approach, the research aims to investigate whether artificial intelligence (AI) will produce the duplication of God's creation. Another important reason of other reseaches on AI is to create a computer which is smart and able to understand human brain working system. Hence, AI has been designed into more practical with faster CPU, cheaper mass memory, and sophisticated software tool. The concept of integrating AI science or collaborative art among sub-fields of technology will stimulate and lead to further AI researches, and it will be an interesting topic for AI researchers for developing AI technology in the future.